Emotional experience in the mornings and the evenings: consideration of age differences in specific emotions by time of day - English, Tammy; Carstensen, Laura (Frontiers in Psychology, 2014)
Considerable evidence points to age-related improvements in emotional well-being with age. In order to gain a more nuanced understanding of the nature of these apparent shifts in experience, we examined age differences in a range of emotional states in the mornings and evenings in a sample of 135 community-residing participants across 10 consecutive days. Participants ranged in age from 22 to 93 years. Each participant completed a diary in the morning and again in the evening every day for the study period. During each of the assessments, participants reported the degree to which they experienced emotions sampled from all four quadrants of the affective circumplex. Overall, participants felt less positive and more negative in the evenings than in the mornings. As expected, older adults reported a relatively more positive emotional experience than younger adults at both times of day. Importantly, however, age effects varied based on emotion type and time of day. Older adults reported experiencing more positive emotion than relatively younger adults across a range of different positive states (although age differences emerged most consistently for low arousal positive states). Age-related reductions in negative experience were observed only for reports of low arousal negative emotions. There were no age differences in anger, anxiety, or sadness. For some emotions, age differences were stronger in the mornings (e.g., relaxed) whereas for other emotions age differences were more pronounced in the evenings (e.g., enthusiastic). Findings are discussed in the context of adulthood changes in motivation and emotional experience.